Fekunditas Ikan Betok (A. testudineus. Bloch) Yang diinduksi dengan hCG dan Hipofisa Ayam Broiler - Melsy Apriadyanti; Muhammad Sugihartono; Muarofah Ghofur (Universitas Batangahari Jambi, 2022)
This study aims to determine the effect of ovulation response on betok fish (A. testudeineus, Bloch) using the combination of the hormone hCG and hypophysis of broiler chickens, this study used a completely randomized design (CRD) with 5 treatments and 3 replications. Where each treatment is given an injection dose: Treatment A: hCG hormone 0.3 ml/kg (100%). Treatment B: 0.225 ml/kg (75%) hCG hormone + 125 ml/kg (25%). Treatment C : 0.15 ml/kg (50%) hCG hormone + 250 ml/kg (50%) broiler hypophysis. Treatment D : Hormone hCG 0.075 ml/kg (25%) + Hypophysis broiler chicken 375 ml/kg (75%). Treatment E: Hypophysis broiler chicken 500 ml/kg (100%). The results showed that the fekundity was 30.552 eggs.